Academic Motivation Scale: adaptation and psychometric analyses for high school and college students - Stover, Juliana Beatriz (Dove Medical Press, 2012)
The Academic Motivation Scale (AMS), supported in Self-Determination Theory, has been applied in recent decades as well in high school as in college education. Although several versions in Spanish are available, the underlying linguistic and cultural differences raise important issues when they are applied to Latin-American population. Consequently an adapted version of the AMS was developed, and its construct validity was analyzed in Argentine students. Results obtained on a sample that included 723 students from Buenos Aires (393 high school and 330 college students) verified adequate psychometric properties in this new version, solving some controversies regarded to its dimensionality.